Plant-available silicon in paddy soils as a key factor for sustainable rice production in Southeast Asia - Klotzbücher, Thimo; Marxen, Anika; Vetterlein, Doris; Schneiker, Janina; Türke, Manfred; Nguyen, Van Sinh; Manh, Nguyen Hung; Van Chien, Ho; Marquez, Leonardo; Villareal, Sylvia; Bustamante, Jesus Victor; Jahn, Reinhold (Elsevier, 2015)
Rice is among the most important crops for human nutrition. The need to increase yields is commonly achieved by agricultural intensification that often comes along with negative impacts on the environment. In 2011, the interdisciplinary LEGATO project was launched with the aim to advance sustainable rice production. A key feature for sustainable rice production is silicon (Si) availability. Si can e.g. improve rice crop resistance against pathogens and prevent the uptake of toxic metals. Herein, we introduce the characteristics of the seven LEGATO study regions in Vietnam and the Philippines (i.e., climate, geology, soils, agricultural practices) ranging from lowlands with intensive production to mountain regions with extensive and traditional production systems. Secondly, we show data on concentrations of plant-available Si (Sipa) in topsoils of paddy fields (Ap + Arp horizons) and of sites with an alternative land-use (forest, upland crops), and discuss factors determining spatial differences in Sipa concentrations. Results show that Sipa concentrations in topsoils of paddies (assessed by acetate extraction) greatly differ between Philippine (141–322 mg Si kg−1) and Vietnamese (20–51 mg Si kg−1) regions. This can be explained by differences in geo-/pedologic conditions between the countries. Large Sipa concentrations in the Philippines are due to recent rock formation by active volcanism, hence, by a large Sipa input due to mineral weathering in recent geologic history. Land-use can also affect Sipa in topsoils: in Philippine regions, Sipa concentrations were significantly larger for paddies than for other land-use types. In some of the Vietnamese paddies, Sipa concentrations are below critical values, thus might limit plant growth. Many Vietnamese farmers export Si from fields by removing straw residues with the harvest. Our subsequent research thus aims to test whether changes in harvest residue management can improve the Si supply to plants in Vietnamese regions